Review Herrera, Miguel, José. Espinosa, y Verónica Orellana. Ruta Pedagógica 2030. Organización de Estados Iberoamericanos para la Educación, la Ciencia y la Cultura, 2021. - Balseca Córdova, Lorena (2022)
This is a review of the book Pedagogical Route 2030 written by Miguel Herrera, José Espinosa, and Verónica Orellana in 2021, which is prepared in support of the COVID-19 Educational Plan: "We learn together at home" of the Ministry of Education in cooperation with the Organization of Ibero-American States for Education, Science and Culture. Organized in coherence with the book, it consists of five parts, the first four referring to the elements and components of the pedagogical model: joint activity based on inquiry, teacher mediation, learning community and approaches, contents and resources, and a fifth part describing, as an example, the ad hoc practical application carried out in times of pandemic, on eight public schools belonging to various regions of Ecuador.